1987
DOI: 10.1093/clinchem/33.7.1217
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of free thyroxin in serum of lactating women.

Abstract: We measured thyroid hormones and thyroxin-binding proteins in serum from 62 normal lactating and 52 nonlactating women at three months postpartum, and compared these values with those for 42 nonpregnant control women of similar age. Mean thyroxin concentrations in the lactating and nonlactating women were significantly (P less than 0.001) lower than that of the nonpregnant controls, but there was no significant difference (P greater than 0.2) in triiodothyronine concentration among these three groups. Free T4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…However, in contrast to our predictions, we found that pregnant and lactating females had lower mT3 concentrations than cycling females. Lower mT3 in lactating female baboons, while in disagreement with data in wild howler monkeys (Dias et al, 2017), agrees with previous reports in humans (Iwatani et al, 1987; Yamamoto et al, 1979). This decrease in T3 levels is unexpected in the context of the high energetic demands of lactation, and may reflect energy conservation strategies on the part of the mother.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, in contrast to our predictions, we found that pregnant and lactating females had lower mT3 concentrations than cycling females. Lower mT3 in lactating female baboons, while in disagreement with data in wild howler monkeys (Dias et al, 2017), agrees with previous reports in humans (Iwatani et al, 1987; Yamamoto et al, 1979). This decrease in T3 levels is unexpected in the context of the high energetic demands of lactation, and may reflect energy conservation strategies on the part of the mother.…”
Section: Discussionsupporting
confidence: 87%
“…We predicted that mT3 concentrations should be lower during the dry season when food availability was reduced, as has been shown by other studies (Ayres et al, 2012; Cristobal-Azkarate et al, 2016; Joly et al, 2015; Schaebs et al, 2016; Wasser et al, 2010; see also review by Chatzitomaris et al, 2017). We also predicted that because of the high energetic costs of pregnancy and lactation, mT3 concentrations should be higher in pregnant and lactating females than in cycling females, as shown for human and non-human primates (Chatzitomaris et al, 2017; Dias et al, 2017; Glinoer, 1997, but see also Iwatani et al, 1987; Yamamoto et al, 1979 for an opposite pattern during lactation in humans).…”
Section: Introductionmentioning
confidence: 68%
“…No specific reference ranges for thyroid function tests are available for LW. Lower mean tT4 concentrations have been reported in LW compared with non-pregnant, non-lactating women ( 29 , 30 ). The thyroid hormone profile in LW resembles hypothyroid or iodine deficiency state with low T4 and low reverse T3 ( 29 ).…”
Section: Discussionmentioning
confidence: 87%